Front Cover: Removing the Hidden Data Dependency of DIA with Predicted Spectral Libraries. Issue 3 (19th February 2020) - Van Puyvelde, Bart; Willems, Sander; Gabriels, Ralf; Daled, Simon; De Clerck, Laura; Vande Casteele, Sofie; Staes, An; Impens, Francis; Deforce, Dieter; Martens, Lennart; Degroeve, Sven; Dhaenens, Maarten
Abstract : DOI: 10.1002/pmic.201900306 In article number 1900306, Van Puyvelde et al. present a unified graphic called the DIAmond DIAgram which the authors use to sample the currently‐available peptide‐centric DIA data analysis strategies and assess their performance. This leads them to an innovative and easily adoptable approach based on predicted spectral information and narrow window DIA. Their contribution removes the current need for DDA prior to DIA analysis, facilitating inter‐laboratory comparison, especially for clinical proteomics.